Penerapan model pembelajaran kooperatif tipe make a match berbantuan media lidimatika untuk meningkatkan keterampilan berhitung perkalian siswa kelas III sekolah dasar - Rahma Wahyu Wijayanti; Matsuri Matsuri (Universitas Sebelas Maret, 2025)
The aim of this study is to describe the steps in implementing the cooperative learning model of the Make A Match type assisted by lidimatika media to improve multiplication skills, as well as to enhance multiplication skills through the application of this model among third-grade students at SDN Dukuhan Kerten. The research subjects were the teacher and third-grade students of SDN Dukuhan Kerten. The data collected consisted of both qualitative and quantitative data. Data collection techniques included observation, interviews, documentation, and tests. Data validation was carried out through source and technique triangulation. Data analysis involved several stages: data collection, data reduction, data presentation, and drawing conclusions. The results show that the implementation of the Make A Match cooperative learning model assisted by lidimatika media led to improvements in each cycle. The percentage of lesson implementation by the teacher increased from 79.58% to 90.83%, while student participation increased from 73.86% to 86.36%. The students’ multiplication calculation test scores also improved from 79.95% in the first cycle to 89% in the second cycle.